Recurrent Acute Pulmonary Toxicity and Respiratory Failure Associated with Fludarabine Monophosphate - Corey Cutler; Yaseen Samman; Richard Fraser; Paul Corris; Arnold Zidulka (Canadian Respiratory Journal)
A case of recurrent acute fludarabine pulmonary toxicity in a 67-year-old man with non-Hodgkin’s lymphoma is presented. The patient responded well to high dose steroid therapy. The literature with respect to this rare entity is reviewed.